Electrode wear phenomenon and its compensation in micro electrical discharge milling: A review. Issue 14 (26th October 2018) - Kar, Siddhartha; Patowari, Promod Kumar
ABSTRACT: Micro electrical discharge machining (µEDM) is playing a significant role in the world of miniaturization, especially in micro electro mechanical systems, biomedical devices, micro die/molds, etc. Micro electrical discharge milling (µED-milling) is a variant of µEDM used for producing complex 3D features with a simple shaped tool. The material removal mechanism of µEDM depends on electro-thermal energy between the tool electrode and workpiece. µEDM inherently being a non-contact machining process, leads to produce miniaturized features in hard to machine materials. Besides erosion of the workpiece material, intrinsic feature of the process leads to tool wear (TW) and introduces dimensional inaccuracy in the micro features. Thus, it is essential to know the factors influencing the TW, and thereby compensate the TW to achieve dimensional stability of the machined features. The critical factors affecting the wear phenomenon of a tool and various techniques applied to compensate TW in µED-milling along with future trends of their application are presented. The key issues of µED-milling and challenges faced in implementing a TW compensation technique are highlighted. The concept of intentional wear of tool electrode and associated advantages in EDM is also demonstrated.